APAKAH RASIO KEUANGAN BERDAMPAK PADA NILAI PERUSAHAAN PERKEBUNAN DI BEI? - Yefni Yefni (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
This study aims to identify the effect of financial ratios, in the form of profitability (ROA), liquidity (CR), and solvability (DER) on firm value. The value of the company was measured using Tobin’s Q. The population of this study were all of the plantation companies listed on the Indonesian Stock Exchange during the 2014-2018. Next, the sample was selected using purposive sampling method. The data in this study were analyzed using multiple linear regression test. The results of this study indicate that of all the variables studied, only ROA and CR have a significant effect on firm value. This shows that profitability and liquidity are the main focus of investors so that investors will pay more attention to these two variables. When a company is profitable and liquid, investors will be interested in investing so that the value of the company will increase.